WORK SAFETY CULTURE TRANSFORMATION AT PT SEMEN PADANG - Indra Mardeni Putra; Aldri Frinaldi (RADJA PUBLIKA, 2023)
The transformation of work safety culture as part of the organizational culture is the company's effort to prevent work accidents so that productivity can be optimized. PT Semen Padang has carried out a work safety culture transformation but still has weaknesses in each element of work safety culture which includes basic assumptions, behavior and organizational situations. This study aims to analyze, reveal the obstacles and efforts that can be made by PT Semen Padang in realizing the transformation of work safety culture. The research approach uses qualitative methods. The research informants were 13 people who were determined by purposive sampling technique. Data were collected by interview, observation and documentation studies and then analyzed using data reduction techniques. presentation of data and drawing conclusions as well as SWOT analysis. The transformation of the work safety culture at PT Semen Padang requires improvement so that it can run effectively. The obstacles encountered were in the aspect of consistency in carrying out policies related to the transformation of work safety culture by all lines within the company. The existence of employee motivation to have a better work safety culture and support from the parent company, namely PT Semen Indonesia Group is a factor that PT Semen Padang can optimize to carry out work safety culture transformation. The obstacles encountered were in the aspect of consistency in carrying out policies related to the transformation of work safety culture by all lines within the company. The existence of employee motivation to have a better work safety culture and support from the parent company, namely PT Semen Indonesia Group is a factor that PT Semen Padang can optimize to carry out work safety culture transformation. The obstacles encountered were in the aspect of consistency in carrying out policies related to the transformation of work safety culture by all lines within the company. The existence of employee motivation to have a better work safety culture and support from the parent company, namely PT Semen Indonesia Group is a factor that PT Semen Padang can optimize to carry out work safety culture transformation.